Larval development of the land hermit crab Coenobita violascens Heller, 1862 (Decapoda, Anomura, Coenobitidae) described from laboratory-reared materia - Kato, Saori; Hamasaki, Katsuyuki; Dan, Shigeki; Kitada, Shuichi (Zootaxa, 2015)
The zoeal and the megalopal stages of the land hermit crab Coenobita violascens Heller, 1862 are described and illustrated from laboratory-reared material, and compared with larvae of nine other described coenobitid species. The larvae developed through four planktonic zoeal stages to the megalopal stage. Coenobita violascens had characteristics of zoeal pleomeres and megalopal antennules typical of those found in other Coenobita species, excluding C. brevimanus.